PENGARUH PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SUMBAWA - Azizati Ainul Haq; Aldi Bahtera; U Usman (Jurnal Ekonomi & Bisnis, 2022)
The aims of this study are: (1) to determine the effect of local taxes on Regional Income (PAD) in Sumbawa Regency; (2) to determine the effect of regional retribution on Regional Income (PAD) in Sumbawa Regency; and (3) to find out the effect of regional taxes and levies together on Regional Income (PAD) in Sumbawa Regency in 2017-2021. This research is an associative research. The analytical tool used in this study is multiple linear regression model analysis with the least squares estimation method (OLS). Based on the results of the analysis that has been carried out, it can be concluded that: (1) local taxes have a positive and significant effect on the one-sided test with a degree of confidence of 0.05% on Regional Income (PAD) in Sumbawa Regency during the period 2017-2021; (2) regional retribution has a positive and significant effect on the one-sided test with a degree of confidence of 0.05% on Regional Income (PAD) in Sumbawa Regency during the period 2017-2021; (3) regional taxes and levies together have a positive and significant effect on the one-sided test with a degree of confidence of 0.05% on Regional Income (PAD) in Sumbawa Regency during the period 2017-2021.